The Everyday Information Practices of New Immigrants to Canada: Findings from the IPEC Study - Caidi, Nadia; Allard, Danielle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This research reports on the preliminary findings from the Information Practices of Ethnocultural Communities (IPEC) research project. IPEC examines the everyday information behaviours and social network practices of new immigrants from Chinese, Indian and Iraninan communities in the Greater Toronto Area (GTA). Cette recherche présente les résultats préliminaires du projet de recherche sur les pratiques informationnelles des communautés ethnoculturelles (IPEC). Le projet IPEC examine les comportements informationnels quotidiens et les pratiques de réseaux sociaux des nouveaux immigrants des communautés chinoise, indienne et iranienne de la grande région urbaine de Toronto.